2021
DOI: 10.1039/d0cp05969b
|View full text |Cite
|
Sign up to set email alerts
|

Conformational structure of cationic tetrahydropyran by one-photon vacuum ultraviolet mass-analyzed threshold ionization spectroscopy

Abstract: Isolating and identifying the conformational forms of molecules are imperative processes to investigate the chemical reaction pathways of individual conformers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…It was previously demonstrated that high-resolution vacuum ultraviolet mass-analyzed threshold ionization (HR VUV-MATI) spectroscopy using a one-photon scheme is effective for exploring the conformational structures of polyatomic molecules as well as their conformer-specific photoionization dynamics and the inducing cationic structure of the conformers. [14][15][16][17][18][19][20][21] In particular, the conformational structures of tetrahydrofuran and tetrahydrothiophene, which are saturated five-membered heterocyclic molecules, were investigated using the constructed potential energy surfaces (PESs) associated with the conformational changes. 14 The replacement of the methylene group in cyclopentane with a heteroatom such as oxygen or sulfur changes the conformational structure, in contrast to the case for cyclopentane.…”
Section: Introductionmentioning
confidence: 99%
“…It was previously demonstrated that high-resolution vacuum ultraviolet mass-analyzed threshold ionization (HR VUV-MATI) spectroscopy using a one-photon scheme is effective for exploring the conformational structures of polyatomic molecules as well as their conformer-specific photoionization dynamics and the inducing cationic structure of the conformers. [14][15][16][17][18][19][20][21] In particular, the conformational structures of tetrahydrofuran and tetrahydrothiophene, which are saturated five-membered heterocyclic molecules, were investigated using the constructed potential energy surfaces (PESs) associated with the conformational changes. 14 The replacement of the methylene group in cyclopentane with a heteroatom such as oxygen or sulfur changes the conformational structure, in contrast to the case for cyclopentane.…”
Section: Introductionmentioning
confidence: 99%
“…14 In general, information about an HOMO can be obtained by examining the geometrical changes induced by ionization, which can be extracted from the vibrational spectrum of the corresponding cation using the Franck-Condon (FC) principle. Recently, VUV mass-analyzed threshold ionization (MATI) spectroscopic investigations of four-, 15,16 five-, 17,18 and sixmembered [19][20][21][22] heterocycles showed well-resolved vibrational peaks in the full vibrational energy range for the corresponding cations. These spectra mostly consisted of symmetry-allowed fundamental bands.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Subsequent investigations have revealed that molecules with a sufficiently low conformer interconversion barrier exist in conformational equilibrium even at low temperatures, [7][8][9] whereas conformers with a high interconversion barrier retain their original composition during cooling via supersonic expansion. [10][11][12] For the former case, identifying peaks that correspond to a specic conformer in measured vibrational spectra requires additional exploration of the vibrational temperature-dependent conformational population, which, in turn, depends on the constructed potential energy surfaces associated with conformational interconversion. Nevertheless, deciphering the contribution of each conformer in the congested vibrational spectrum of a polyatomic molecule is still immensely difficult because of the comparable force elds between the atoms in conformers.…”
Section: Introductionmentioning
confidence: 99%